Simultaneous measurement of detonation velocity and detonation front curvature using fiber optic probe - Künzel, Martin; Vodochodský, Ondřej; Kučera, Jindřich; Pachman, Jiří (Univerzita Pardubice, 2019)
The paper describes a novel technique of measurement of two key parameters of detonation wave, velocity and front curvature, at the same section of a cylindrical explosive charge. The measurement technique utilizes a perforated fiber optic probe which crosses the tested charge under an angle of 45°. Small holes drilled in the probe core act as air voids and produce light pulses upon arrival of the detonation wave. Curved front of the detonation wave passing along this probe causes nonlinear time distribution of the light pulses which can be analyzed to determine both detonation velocity and shock front curvature. The technique was tested on melt casted charges of erythritol tetranitrate and also on a powdered mixture of ammonium nitrate and aluminium. The resulting detonation velocity was in a perfect agreement with previously measured and calculated values.
Simultánní měření detonační rychlosti a zakřivení čela detonační vlny pomocí vláknové optické sondy
Keywords: Fiber optic probe, Detonation front curvature, Detonation velocity, Erythritol tetranitrate; Plastová optická sonda; Zakřivení čela detonační vlny; Detonační rychlost; Erytritol tetranitrát